Improved production technology and efficiency of smallholder farmers in Ethiopia : Extended parametric and non-parametric approaches to production effeciency analysis - Hassan, Rashid M. (University of Pretoria, 2013)
Thesis (PhD (Agricultural Economics))--University of Pretoria, 2007.